2006
DOI: 10.1140/epje/i2006-10053-9
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity banding during the lamellar-to-onion transition in a lyotropic surfactant solution in shear flow

Abstract: We report on the rheology of a lyotropic lamellar surfactant solution (SDS/dodecane/pentanol/ water), and identify a discontinuous transition between two shear thinning regimes which correspond to the low-stress lamellar phase and the more viscous shear-induced multilamellar vesicle, or "onion" phase. We study in detail the flow curve, stress as a function of shear rate, during the transition region, and present evidence that the region consists of a shear-banded phase where the material has macroscopically se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 56 publications
(98 reference statements)
1
31
1
Order By: Relevance
“…Gradient shear banding, that is the occurence of bands with different shear rates, stacked along the velocity gradient, is a likely scenario during the inhomogeneous MLV-to-layer transition [16] since MLVs and aligned lamellae have different viscosities. There has also been a report on the observation of vorticity shear banding, i.e., of bands of different stress stacked along the vorticity axis, during the lamellar-to-onion transition [61] but we have seen no evidence B. Medronho et al of this in our NMR studies.…”
Section: Introductioncontrasting
confidence: 59%
“…Gradient shear banding, that is the occurence of bands with different shear rates, stacked along the velocity gradient, is a likely scenario during the inhomogeneous MLV-to-layer transition [16] since MLVs and aligned lamellae have different viscosities. There has also been a report on the observation of vorticity shear banding, i.e., of bands of different stress stacked along the vorticity axis, during the lamellar-to-onion transition [61] but we have seen no evidence B. Medronho et al of this in our NMR studies.…”
Section: Introductioncontrasting
confidence: 59%
“…Vorticity banding is some times observed when discontinuous (or very strong) shear thickening occurs (like for the worm-like micelles in Bonn et al 1998, Wilkins and Olmsted 2006, and Fischer et al 2002, where the shear stress exhibits a (quasi-)discontinuity, like in Fig. 10b (but not necessarily followed by shear thinning).…”
Section: Vorticity Bandingmentioning
confidence: 95%
“…The bands that are stacked along the vorticity direction (as sketched in the right Fig. 1) are visible either due to differences in optical birefringence (like for the rodlike colloids in Dhont et al 2003 andKang et al 2006) and the onions in Wilkins and Olmsted (2006) or turbidity (like the worm-like micelles in Fischer et al 2002). In some of these systems (Bonn et al 1998;Chen et al 1992), a van der Waals loop in the stress is found, so that it seems that both gradient and vorticity banding can occur.…”
Section: Vorticity Bandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow-induced pattern formation leading to banded regions is a quite general phenomenon in complex fluids, being found in wormlike micellar solutions [1], rodlike virus suspensions [2], attractive emulsions [3], lyotropic liquid crystals [4], suspensions of rigid spherical particles [5], supramolecular polymer solutions [6], and granular materials [7]. Band formation in complex fluids has been mostly studied in shear flow, which is shown schematically in Fig.…”
mentioning
confidence: 99%